Supply Chain Strategy for Developing the Fishery Industry in Aceh Province, Indonesia - Jumadil Saputra; Rahimah Khairi Isfani; Said Muhammad; Abd Jamal; Muhammad Nasir (International Journal of Supply Chain Management, 2020)
The fishery sector is one of the main contributors to the economic growth of the region. It plays a significant role in sustainable livelihoods and poverty reduction in several households and communities. The purpose of this study is to investigate the supply chain strategy for developing fishery industry in Aceh province and examine the mediating role of competitive advantage in the relationship between service quality and fishery industry performance, Indonesia. This cross-sectional study through a questionnaire self-administered conducted on three fishery harbours in Aceh. A total of 150 fishermen had participated in this study, the data collected by using purposive sampling. The data analysed by utilizing the Structural Equation Modelling (SEM) via Analysis of Moment Structure (AMOS). The results of this study found that external factor and service quality have direct effect significant on competitive advantage. Further, the external factor, natural resource and energy and internal factor have direct effect significant on fishermen capabilities. In addition, we also found that the competitive Advantage and Internal Factor have a significant direct effect on fishery industry performance. In contrast, this study found that natural resource and energy and service quality do not significant effect directly on fishery industry performance. Also, after conducting the mediating test, we found that competitive advantage has mediated the relationship between service quality and fishery industry performance. Using the Multi-Group Analysis (MGA), this study found that the role of Panglima Laot (as leader of fishery community) does not important for fishery industry performance.Keywords Supply chain strategy, fishery industry performance, service quality, competitive advantage, natural resource and energy, fishermen capabilities, Panglima Laot.